Financial Fraud, Independent Female Directors and CEO Power - Nafisah Yami; Jannine Poletti-Hughes (Journal of Risk and Financial Management, 2022)
This paper investigates the effect of female directors on financial fraud, focusing on the role of independent female directors and their demographics, such as experience, financial expertise, and audit committee membership. We find that independent female directors have a negative and significant influence on financial fraud, which is enhanced by their experience and financial expertise. The positive effect is also significant for those female directors that are members of the audit committee and have financial expertise. Independent female directors offset the increased likelihood of fraud in the presence of powerful CEOs, suggesting that the impact of their contribution is more valuable when there is managerial entrenchment.
Keywords: 650; CEO power; gender diversity; financial fraud; independent female directors